Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/1745-9133.12066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Implications of Sex Offender Residence Restrictions

Abstract: M i c h i g a n S t a t e U n i v e r s i t y Eric Grommon I n d i a n a U n i v e r s i t y -P u r d u e U n i v e r s i t y I n d i a n a p o l i s Breanne Pleggenkuhle S o u t h e r n I l l i n o i s U n i v e r s i t y -C a r b o n d a l e Research SummaryWe evaluated the efficacy of sex offender residence restrictions in Michigan and Missouri using a quasi-experimental design with propensity score matching. First, we examined the implementation of the laws and found that sex offenders in both states were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 69 publications
0
57
0
Order By: Relevance
“…In the United States of America residence restrictions for known sex offenders were implemented in several states and municipals in order to reduce reoffending. Residence restriction means that a child sex offender is not allowed to seek residence within 1.000 to 2.500 feet of schools, playgrounds and other facilities often visited by children (Huebner et al, 2014). This generally received great support from within society.…”
Section: Attitudes Towards Sex Offendersmentioning
confidence: 99%
“…In the United States of America residence restrictions for known sex offenders were implemented in several states and municipals in order to reduce reoffending. Residence restriction means that a child sex offender is not allowed to seek residence within 1.000 to 2.500 feet of schools, playgrounds and other facilities often visited by children (Huebner et al, 2014). This generally received great support from within society.…”
Section: Attitudes Towards Sex Offendersmentioning
confidence: 99%
“…Previous research shows that registered sex offenders do have difficulties in finding and establishing housing due to the sex offender registration and notification, as well as the residency restriction laws (Huebner et al, 2014;Levenson & Cotter, 2005a;Levenson, D'Amora & Hern, 2007;Mustaine, 2014;Tewksbury, 2005). This study found that nearly half (44.1%) of the homeless shelters were within 1000' of a school, therefore making them off limits to sex offenders because it would violate the residency restriction laws of each state in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, SORN has made the reintegration process for sex offenders extremely difficult, because it limits their options in housing, employment, social support, and education (Barnes, Dukes, Tewksbury & De Troye, 2009;Chajewski & Mercado, 2009;Duwe, Donnay & Tewksbury, 2008;Dyck & Hagley, 2012;Farkas & Miller, 2007;Huebner, Kras, Rydberg, Bynum, Grommon & Pleggenkuhle, 2014;Levenson, 2008;Levenson, D'Amora & Hern, 2007;Logan, 2009;Mercado, Alvarez & Levenson, 2008;Mustaine & Tewksbury, 2011;Tewksbury, 2005;Zandbergen & Hart, 2006).…”
Section: Chapter II Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations